Working with Local Researchers - Manning, Ryann (World Bank, Washington, DC, 2018)
Training local researchers to conduct high-quality qualitative research in a country like Sierra Leone is both a time and resource-intensive task. However, there are many benefits to partnering with a local organization which cannot be replicated or replaced by simply hiring ready-made international researchers. First, the J4P project in Sierra Leone has received a great deal of appreciation locally for its decision to work closely with a national partner, and its commitment to building local research capacity. Second, and related to the first, it is quite possible that these local partnerships increase the likelihood that the research will have an impact on policy and programs here in Sierra Leone, particularly those instituted locally by government or civil society actors. Finally, there is much that local researchers themselves teach the project. They often provide a reality-check on research instruments and methods before they are field-tested. This briefing note focuses on the experience to date in Sierra Leone, where the project has been working in partnership with a local Non Governmental Organization (NGO), the Campaign for Good Governance (CGG), and with a team of local researchers hired by CGG.